Effect of dietary roasted and autoclaved full‐fat soybean on the performance of laying hens and egg quality traits - Zohreh Karimi; Mehran Torki; Alireza Abdolmohammadi (Veterinary Medicine and Science, 2022)
Abstract Context Full fat soybean (FFSB) can be used in poultry diets as a source of fat and protein, without extra cost for oil extraction; however, raw FFSB contains several anti‐nutritional factors. Aims Investigating the effects of replacing dietary soybean meal (SBM) with processed (roasted or autoclaved) FFSB on the performance of laying hens and egg quality traits. Methods A total of 324 Bovans White strain laying hens were randomly selected and distributed in 54 replicate cages. Based on a completely randomized design with a 2 × 4 factorial arrangement of treatments plus a control group, nine diets in which SBM were replaced with 25%, 50%, 75% and 100℅ roasted or autoclaved FFSB, with six replicates (with six hens each), were evaluated during an 8‐week trial period (60–68 weeks). Key results Significantly increased feed intake (FI) was observed in hens fed diets including autoclaved FFSB (p < 0.05). The interactions between SBM replacement level and processing on feed conversion ratio (FCR), egg production (EP) and egg mass (EM) were significant (p < 0.01). Hens fed the diet with 100% roasted FFSB instead of SBM showed poor performance in terms of FCR, EP and EM during the experimental period. The main effect of SBM‐replacing level on Haugh unit was significant (p < 0.05). The main effect of processing on shell thickness was significant (p < 0.05), so autoclaved FFSB caused higher eggshell thickness than control and roasted FFSB. Conclusions Replacement of dietary SBM with autoclaved FFSB can improve laying hens’ performance in terms of FCR, EP, EM and eggshell quality and yolk colour. Implications The use of autoclaved FFSB to replace commercial SBM and its oil in the diet of laying hens is recommended. Feed factories can formulate the diets of laying hens with autoclaved FFSB without extra cost due to oil extraction soybeans.